Projected changes in atmospheric river events in Arizona as simulated by global and regional climate models - Rivera Fernández, Erick (2015)
Inland-penetrating atmospheric rivers (ARs) affect the United States Southwest and significantly contribute to cool season precipitation. In this study, we examine the results from an ensemble of dynamically downscaled simulations from the North American Regional Climate Change Assessment Program (NARCCAP) and their driving general circulation models (GCMs) in order to determine statistically significant changes in the intensity of the cool season ARs impacting Arizona and the associated precipitation. Future greenhouse gas emissions follow the A2 emission scenario from the Intergovernmental Panel on Climate Change Fourth Assessment Report simulations. We find that there is a consistent and clear intensification of the ARrelated water vapor transport in both the global and regional simulations which reflects the increase in water vapor content due to warmer atmospheric temperatures, according to the Clausius-Clapeyron relationship. However, the response of AR-related precipitation intensity to increased moisture flux and column-integrated water vapor is weak and no significant changes are projected either by the GCMs or the NARCCAP models. This lack of robust precipitation variations can be explained in part by the absence of meaningful changes in both the large-scale water vapor flux convergence and the maximum positive relative vorticity in the GCMs. Additionally, some global models show a robust decrease in relative humidity which may also be responsible for the projected precipitation patterns.